A Novel Weight Based Interest Forwarding Protocol for Information Centric Networking - Delvadia, Krishna (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Information centric network (ICN) is a new communication paradigm that is introduced to satisfy the needs of internet users in context of throughput and delay. Content request routing is an important research domain of content centric network. If request is routed efficiently within network, then retrieval of desired content is possible in least duration with less overhead. This paper introduces a weight-based interest forwarding strategy that aims to route interest message towards content router (CR) having maximum likelihood of having desired data. This can significantly contribute in reduction of latency and overhead. The protocol exploits three different parameters namely interest packet forwarding ratio, size of node’s pending interest table (PIT) and count of data messages produced by router to take decision for interest packet forwarding. The experimental analysis of proposed strategy is done inside ndnSIM 2.0. The performance testing of state-of-the-art caching mechanisms with and without inclusion of proposed protocol in context of data discovery delay, overhead and content store (CS) hit ratio. We have also compared the integrated variants of protocols against recent existing forwarding protocols. The extensive simulation study proves that the coupling of proposed mechanism to existing mechanisms remarkably enhances the performance by 10-42%.